(3Med GdefGaSGJ Ydi GdeJWdHGJ GdHOfjI h GdaSjhdhLjI h GdegGQjI dOi dGYHj cQI GdbOe (B: (3OQGSI ejOGfjI Ydi aQjb GJMGO GdTGhjI Ufa GcGHQ (B20 - 35 (3SfI s - (3eSYhOj, YHO GdQMeGfs; (3eGghQ HGTG, UHjQIs; (3eYgO GdJQHjI GdHOfjI h GdQjGVjI, LGeYI GdLRGFQ (B3 s ((3GdLRGFQ s, 2022)
(3cGf GdgOa ef GdOQGSI gh eYQaI JCKjQ Med cKGaI GdefGaSGJ Ydi HYV GdYfGUQ GdHOfjI h GdajSjhdhLjI hGdegGQjI hGSJNOe GdHGMK GdefgL GdhUaj dedGAeJg WHjYI GdOQGSI hgPG HYO JWHjb HQfGeL eJGHYI Ref eTGQcI cd dGYH aj LejY GdeHGQjGJ GdJj HdZJ (B( 21) (3ebGHdI (B6 (3ebGHdGJ NGUI HJUajGJ cCS GdLeghQjI h (B(15)(3ebGHdI NGUI HGdHWhdI HRef cdj MLeg (B2120 (3ObjbI NdGd eQMdI GdPgGH ,MjK Jchf eLJeY GdOQGSI ef dGYHj cQI GdbOe Ydi eSJhi bSe ghGI hGdHGdZ YOOge (B16 (3aQjb MSH EMUGAjGJ cQI GdbOe dYGe (B2018/2019.(3hJe GNJjGQ GdYjfI HWQjbI bUOjI h JeKdJ aj dGYHj cQI GdbOe CcGHQ dfGOj GJMGO GdTGhjI YOOge (B24 (3Je JbSjege HMSH Ref GdeTGQcI aj GdeHGQjGJ Edi YjfJjf, GdYjfI GdChdi gj YjfI GddGYHjf GdCSGSjjf (B((3fSHI GdeTGQcI ahb (B50 % (3ef GdRef Gdcdj ddefGaSGJ(B)(3h GdYjfI GdKGfjI gj YjfI GddGYHjf GdGMJjGWjjf (B((3fSHI GdeTGQcI Cbd ef (B50 % (3ef GdRef Gdcdj ddefGaSGJ(B)(3, MjK Je JWHjb eLehYI ef GdGNJHGQGJ GdHOfjI hGdajShdhLjI hGdegGQjI (B((3GdbhI, GdSQYI GdGfJbGdjI ,GdSQYI GdghGFjI, GdfHV GdbdHj , QejI GdJeGS , JUhjH GdcQI (B...(3GdN(B)(3bHd hHYO eQMdI GdPgGH hJe VHW GdYhGed GdeDKQI Ydi GdLGfH GdHOfj ddGYHjf hgj(B: (3GdJMVjQ GdHOfj , GdJZPjI , GdMUU GdJOQjHjI NdGd eQMdI GdPgGH, hJe JMdjd fJGFL GdHMK Yf WQjb GSJNOGe GdhSGFd GdGMUGFjI GdefGSHI (Bspss . (3h JhUd GdHGMK Edi hLhO aQhb OGdI EMUGFjG YfO GdebGQfI Hjf GdGNJHGQGJ GdHOfjI GdbHdjI h GdHYOjI dOi GdYjfI GdChdi (B((3GdGYHjf GdGSGSjf(B)(3,hGSJfJL GdHGMK Ydi Gf Med GdefGaGSGJ COi Gdi JRGjO GdbhI GdGfaLGQjI ddLRA GdYdhj h GdSadj ebGQfI HGddGYHjf GdGMJjGWjjf hcPdc egGQI GdJUhjH h QejI GdJeGS , ceG JDOj cKGaI GdefGaSGJ Edi MOhK RjGOI aj GdSQYI GdghGFjI GdbUhi hGdGSJgdGc GdCbUi ddChcSLjf hSQYI GdCSJQLGY dOi GddGYHjjf GdCSGSjjf ebGQfI HGdGMJjGWjjf(B. (3hChUi GdHGMK HJfXje MehdI h GTQGc LejY GddGYHjjf NdGd GdefGaGSGJ (B((3GdHWhdI GdhWfjI,cCS GdLeghQjI (B) (3MSH LgO GddGYHjf ddeMGaXI GdfSb hGdTOI GdJcJjJcjI dOi GddGYHjf hcPdc GdCYJeGO Ydi hSGFd GdGSJQLGY GdeNJdaI(B. - (3ELQGA OQGSGJ Mhd cKGaI GdefGaSGJ Ydi HGbj GdUaGJ GdHOfjI hGdajSjhdhLjI hGdegGQjI GdCNQi(B. (3GdcdeGJ GdOGdI (B:(3Med GdefGaSGJ, GdeJWdHGJ GdHOfjI, GdeJWdHGJ GdajSjhdhLjI, GdLGfH egGQj , cQI GdbOe,Ufa CcGHQ(B. s
(3OcJhQGIs
Keywords: (3GdJMVjQ GdHOfj GdQjGVjs; (3GdaSjhdhLjGs; (3cQI GdbOes